Short-term stability of lysergic acid diethylamide (LSD), N-desmethyl-LSD, and 2-oxo-3-hydroxy-LSD in urine, assessed by liquid chromatography-tandem mass spectrometry - Skopp, Gisela; Pötsch-Schneider, Lucia Edeltraud; Mattern, Rainer; Aderjan, Rolf (Clinical chemistry, 2002)
Lysergic acid diethylamide (LSD) is one of the most potent hallucinogenic agents known. Recently, data on emergency department episodes related to the use of drugs commonly thought as “club drugs” have also included LSD (1). Confirmation of LSD use by testing biological fluids is still an analytical challenge because of its extensive, rapid metabolism and its instability (2)(3)(4). After ingestion of a typical street dose (40-120 μg), the concentration of LSD in urine falls to <1 μg/L within a few hours (2)(5)(6). Recently, N-desmethyl-LSD (nor-LSD) and 2-oxo-3-hydroxy-LSD (O-H-LSD) have been identified as LSD metabolites in human urine (7)(8). Measured nor-LSD concentrations were reported to be in the same concentration range as LSD, whereas the measured concentrations of O-H-LSD were severalfold higher (0.02-21.4 μg/L) (7)(9)(10)(11). The application of liquid chromatography-tandem mass spectrometry (LC-MS/MS) improved the detection of LSD use (9)(10)(12)(13)(14)(15); the method is also less susceptible to interferences when used for drug screening (16)(17). In a few studies, O-H-LSD and nor-LSD have also been measured (6)(7)(8)(10)(12)(13)(14)(15). LSD has been shown to rapidly decompose in urine samples exposed to an increased temperature or to sunlight or ultraviolet light (18)(19)(20)(21), but stability data on major LSD metabolites are not yet available.